2010
DOI: 10.1029/2010ja015413
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term neutron monitor observations and the 2009 cosmic ray maximum

Abstract: [1] The solar minimum of 2009 was characterized by a prolonged increase toward the maximum cosmic ray intensity, which was higher than it was during the maxima of 22 and 44 years ago. In the previous two so-called qA <0 (solar dipole moment facing South) magnetic cycles, these increases were more sharply peaked than in 2009. The observations of the Sanae, Hermanus, Potchefstroom, and Tsumeb neutron monitors are used to investigate this behavior in terms of propagation conditions due to solar activity, the heli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 25 publications
4
39
0
Order By: Relevance
“…An interesting feature is related to the recent decade. The CR flux in 2009 was the highest ever recorded by NMs (Moraal and Stoker 2010), as caused by the favorable heliospheric conditions (unusually weak heliospheric magnetic field and the flat heliospheric current sheet) (McDonald et al 2010). On the other hand, the sunspot minimum was comparable to other minima.…”
Section: Heliospheric Modulation Of Cosmic Raysmentioning
confidence: 99%
“…An interesting feature is related to the recent decade. The CR flux in 2009 was the highest ever recorded by NMs (Moraal and Stoker 2010), as caused by the favorable heliospheric conditions (unusually weak heliospheric magnetic field and the flat heliospheric current sheet) (McDonald et al 2010). On the other hand, the sunspot minimum was comparable to other minima.…”
Section: Heliospheric Modulation Of Cosmic Raysmentioning
confidence: 99%
“…Indeed, the GCR intensity values measured by neutron monitors were the highest ever recorded (e.g. Moraal and Stoker, 2010;Oh et al, 2013). In 2007, neutron monitors (NMs) recorded values last measured during the last A < 0 solar minimum, 1985 -1987, and the values continued to grow, exceeding the previous levels by a few percent, throughout the end of 2009.…”
Section: Introductionmentioning
confidence: 99%
“…It was ascribed to the anomaly increasing the diffusion of cosmic rays (Moraal and Stoker, 2010) during the Minimum 23/24. Dunzlaff et al (2008) reported, based on Ulysses observational data, that in SC 22 the decrease in the component of the recurrent GCR arising from the fast solar wind showed a visible maximum from 25 • to 40 • and beyond, but in SC 23 there was no such substantial change.…”
Section: Introductionmentioning
confidence: 99%
“…stations are showing GCR fluxes that are equalling the previous record high (Moraal et al 2009). In addition, the long sequence of BiSON helioseismology data is revealing larger changes in the solar interior than seen in previous minima (Broomhall et al 2009).…”
Section: Some Basic Considerationsmentioning
confidence: 99%